If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = Log(4x + 12) Multiply f * x fx = Log(4x + 12) Reorder the terms: fx = goL(12 + 4x) fx = (12 * goL + 4x * goL) fx = (12goL + 4goxL) Solving fx = 12goL + 4goxL Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 12gox-1L + 4goL Simplifying f = 12gox-1L + 4goL Reorder the terms: f = 4goL + 12gox-1L
| 2-10=x/-7 | | 2a-4b+3b+3a= | | 3a^5-39a^3+108a=0 | | 4a-2x+7a-x= | | 2y=-13(x-5) | | 2x-3y+x-4y= | | 3x-5y-(-3x)= | | 3a+b-(-2b)= | | 4a-5c+3a-c= | | 2a+3x-4x-5a= | | 9+b=c+3a | | -2(x-1)=-2x-(x+4) | | 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= | | 2*(3a)= | | -24+x=36 |